Impact of Financial Inclusion on Monetary Policy Effectiveness: Evidence from Pakistan - Tariq Majeed,; Ibrar Hussain,; Aftab Alam,; Azmat Hayat,; Muhammad Azhar, (Dialogue Social Science Review (DSSR), 2025)
Effective monetary policy controls inflation, reduces unemployment, strengthens economic growth, and brings economic stability. To examine whether this channel works in the case of Pakistan, we have designed this study to investigate the impact on the monetary policy effectiveness of financial inclusion (FI). The inflation rate is used as a proxy for the monetary policy's effectiveness. The FI index is constructed, through principal component analysis, by utilizing the demand and supply sides indicators of FI proposed by the International Monetary Fund. The augmented ARDL bounds test results confirmed the co-integration relationship among the variables. The ARDL model results indicate, both in the long run and short run, that FI has a negative and significant effect on the inflation rate. It means that FI contributes to the improvement in the monetary transmission mechanism, which in turn makes the monetary policy more effective. Exchange rate has a positive and significant impact on the inflation rate, both in the short run and the long run. The lending rate, GDP growth, and broad money supply have no significant impact on the effectiveness of monetary policy. The long-run Granger causality test indicated that causality runs from FI to the effectiveness of monetary policy. In short, we concluded that FI contributes significantly to the improvement of monetary policy effectiveness. This study recommends that policymakers should encourage the access of poor and marginalized adults to financial services and products to improve the monetary policy's effectiveness and bring stability to the price level and the economy. The study also extended and applied the Phillips (2016) framework for the selection of the ARDL bounds model to the selection of the augmented ARDL bounds model.